Silicon fluoride rubber and preparation method thereof

By grafting perfluorodecyl mercaptan (PFDT) onto the side chains of methyl vinyl silicone rubber (MVQ), the problems of low-temperature crystallization and low polarity of MVQ were solved, achieving fluorination modification and improving low-temperature performance and oil resistance.

CN120818145APending Publication Date: 2025-10-21BEIJING UNIV OF CHEM TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410438788.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-12
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

Methyl vinyl silicone rubber (MVQ) is prone to crystallization at low temperatures, which causes it to lose its performance. In addition, its molecular chain polarity is poor, which affects its application in the field of oil-resistant sealing.

Method used

Perfluorodecyl mercaptan (PFDT) is grafted onto the side chain of MVQ via a mercapto-olefin click chemistry reaction, thereby achieving fluorination modification of MVQ, disrupting the regularity of the molecular chain, and introducing a highly polar side group.

Benefits of technology

The low-temperature crystallization phenomenon of MVQ was successfully suppressed, improving its application performance in low-temperature environments, and increasing the polarity of the molecular chain, thus enhancing its oil resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818145A_ABST
    Figure CN120818145A_ABST
Patent Text Reader

Abstract

The invention discloses silicon fluoride rubber and a preparation method thereof, and relates to the technical field of rubber functional modification.The preparation method of the silicon fluoride rubber comprises the steps that methyl vinyl silicone rubber is dissolved in a solvent, then perfluorodecanethiol and a photoinitiator are added, a grafting reaction is initiated by adopting an ultraviolet light source in a closed environment, and the silicon fluoride rubber is obtained; after the grafting reaction is finished, flocculating and drying to obtain the silicon fluoride rubber. Starting from molecular structure design, MVQ is subjected to fluorination grafting modification. Through a simple, convenient and efficient sulfydryl-alkene click chemical reaction, a highly polar PFDT group is introduced to an MVQ molecular chain to prepare MVQ-g-PFDT. Because the polarity side group PFDT destroys the regularity of a silicon-oxygen main chain, the low-temperature crystallization phenomenon of MVQ is successfully inhibited. The fluorinated modified MVQ has a wide application prospect in a low-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of rubber functional modification, and more particularly to a fluorinated silicone rubber and a preparation method thereof. Background Art

[0002] With the rapid consumption of global fossil energy and the continuous growth of carbon emissions, the dual pressures of resource shortage and environmental pollution are driving the research and development and application of green energy materials. As a green material that does not consume fossil energy, silicone rubber has attracted much attention due to its excellent weather resistance, electrical insulation and biocompatibility. Methyl vinyl silicone rubber (MVQ) is widely used due to its excellent vulcanization properties and resistance to permanent compression set. However, because the MVQ molecular chain is too regular, it easily crystallizes at low temperatures, losing some of its performance, and its use in low-temperature environments is limited. Secondly, the methyl and vinyl side groups of MVQ are both non-polar groups, so its molecular chain has poor polarity and poor oil resistance, which affects its application in the field of oil-resistant seals. Summary of the Invention

[0003] To address the problems existing in the prior art, the present invention provides a fluorinated silicone rubber and a method for preparing the same. This invention addresses the low-temperature crystallization and low polarity issues of silicone rubber by grafting perfluorodecanethiol (PFDT) onto the side chains of MVQ via a mercapto-ene click chemistry reaction, achieving fluorination modification of MVQ.

[0004] One of the objects of the present invention is to provide a fluorinated silicone rubber.

[0005] The structural formula of the fluorinated silicone rubber of the present invention is:

[0006]

[0007] Wherein, x is the methyl content, which is 85-100 mol%, preferably 89-91 mol%; y is the vinyl content, which is 0-5 mol%, preferably 0.05-2 mol%; and z is the PFDT side chain content, which is 0-15 mol%, preferably 8-11 mol%.

[0008] A second object of the present invention is to provide a method for preparing the fluorinated silicone rubber as described in one of the objects of the present invention.

[0009] The preparation method of the fluorinated silicone rubber of the present invention comprises:

[0010] The methyl vinyl silicone rubber is dissolved in a solvent, and then perfluorodecanethiol and a photoinitiator are added. A grafting reaction is initiated in a closed environment using an ultraviolet light source. After the grafting reaction is completed, flocculation and drying are performed to obtain the fluorinated silicone rubber.

[0011] In a preferred embodiment of the present invention:

[0012] The vinyl content of the methyl vinyl silicone rubber is 5-15 mol%, preferably 9-11 mol%, and / or the number average molecular weight is (25-35)×10 4 g / mol, preferably (27-33)×10 4 g / mol, and / or, a molecular weight distribution of 1.0-2.0, preferably 1.5-1.9.

[0013] The methyl vinyl silicone rubber is a methyl vinyl silicone rubber commonly used in this field. For details, please refer to the existing technology: Zhang Weizhen. Synthesis of epoxidized silicone rubber and preparation and application research of its composite materials [D]. Beijing University of Chemical Technology, 2023. Prepared.

[0014] In a preferred embodiment of the present invention:

[0015] The solvent is at least one of tetrahydrofuran, dichloromethane and chlorobenzene.

[0016] In a preferred embodiment of the present invention:

[0017] The photoinitiator is at least one of benzoin dimethyl ether, 2-hydroxy-2-methylphenyl acetone, 4-chlorobenzophenone (CBP), and 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide (TPO).

[0018] In a preferred embodiment of the present invention:

[0019] The concentration of the methyl vinyl silicone rubber after being dissolved in the solvent is 1-10 g / 50 ml, preferably 3-6 g / 50 ml.

[0020] In a preferred embodiment of the present invention:

[0021] The molar ratio of vinyl groups in the methyl vinyl silicone rubber to perfluorodecanethiol is 1:(0.8-3), preferably 1:(1.2-1.5).

[0022] In a preferred embodiment of the present invention:

[0023] The molar ratio of vinyl to photoinitiator in the methyl vinyl silicone rubber is 1:(0.005-0.05), preferably 1:(0.01-0.02). An appropriate amount of photoinitiator can achieve the initiation effect and reduce the amount of initiator residue in the product.

[0024] In a preferred embodiment of the present invention:

[0025] The dissolution is carried out by magnetic stirring to accelerate the dissolution speed, with a rotation speed of 300-400 r / min; and / or,

[0026] The ultraviolet light source can be a commonly used ultraviolet light source in the art, such as a wavelength of 365 nm and an intensity of 1 to 10 mW / cm 2 Selecting the appropriate UV light source, wavelength and intensity to achieve the best initiation effect; and / or

[0027] The reaction temperature of the grafting reaction is 22° C.-25° C., and / or the reaction time is 1-15 minutes.

[0028] The following solutions can be adopted:

[0029] MVQ is added to the solvent to fully dissolve it, and then PFDT and a photoinitiator are added. In a closed chamber, a surface light source ultraviolet lamp with a wavelength of 365nm is used to induce the grafting reaction. After the grafting reaction is completed, the reaction solution is poured into anhydrous ethanol and / or anhydrous methanol, and the product is flocculated by adding a poor solvent. MVQ-g-PFDT is obtained by flocculation, and then it is redissolved in THF and flocculated again to remove the initiator and unreacted small molecules. After repeating three times, the product is placed in a vacuum oven at 55°C and vacuum-dried to constant weight to remove the solvent to obtain the final product. The vacuum pressure is -0.098MPa. Under vacuum and high temperature conditions, the drying efficiency of the product can be improved. Among them, the volume ratio of the reaction solution to the amount of anhydrous ethanol and / or anhydrous methanol is 1: (1.5-2). Adding excess poor solvents can increase the amount of product flocculation and improve the yield. In order to improve the purity of the product and reduce the residual amount of photoinitiator, the flocculation process is repeated three times. The specific reaction equation is as follows

[0030]

[0031] Wherein, x represents the methyl group content (the content remains unchanged before and after the reaction), y' represents the vinyl group content before the reaction, z represents the PFDT group content after the reaction, y represents the vinyl group content after the reaction, and y=y'-z.

[0032] The third object of the present invention is to provide a fluorinated silicone rubber prepared by the preparation method as described in the second object of the present invention.

[0033] This invention utilizes molecular structure design to graft fluorinated MVQ. Through a simple and efficient thiol-ene click chemistry reaction, highly polar PFDT groups are introduced into the MVQ molecular chain to prepare MVQ-g-PFDT. The polar PFDT side groups disrupt the regularity of the silicon-oxygen backbone, successfully suppressing low-temperature crystallization of MVQ. Fluorinated MVQ has broad application prospects in low-temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1This is the H NMR spectrum of MVQ-g-PFDT prepared in Example 1;

[0035] Figure 1 The chemical shifts corresponding to the groups in the reaction are as follows: δ = 5.59 to 5.69 ppm and δ = 5.74 to 5.90 ppm are the chemical shifts of hydrogen on -CH = and =CH2 in the vinyl group, respectively; δ = 0.07 ppm is the methyl hydrogen peak in the dimethyl structural unit; and δ = 0.14 ppm is the methyl hydrogen peak in the vinyl structural unit, which proves the existence of the basic structure of MVQ; a -CH2- hydrogen chemical shift connected to Si appears at δ = 0.84 ppm, δ = 2.61 ppm and δ = 2.72 ppm are the two -CH2- hydrogen chemical shifts connected to S, and δ = 2.34 ppm is the -CH2- hydrogen chemical shift connected to -CF2. The appearance of the two methylene peaks connected to S proves that the thiol-ene reaction has successfully grafted PFDT onto the side chain of silicone rubber, and MVQ-g-PFDT has been successfully synthesized.

[0036] Figure 2 DSC curves of methyl vinyl silicone rubber (MVQ), MVQ-g-PFDT prepared in Example 1, Example 5, and Example 6 in a nitrogen atmosphere;

[0037] Figure 2 It can be seen that compared with MVQ, the glass transition temperature (Tg) of MVQ-p-PFDT shows a significant upward trend, rising from -125.9°C to -123.5°C~-122.0°C. This is because the introduction of polar side groups reduces the flexibility of the silicone rubber molecular chain, thereby causing the Tg to rise; MVQ shows a clear crystalline melting peak (Tm) at -58.3°C, which indicates that MVQ with a high vinyl content is prone to crystallization in a low-temperature environment due to the good regularity of its polymer chain; the crystalline melting peak of MVQ-g-PFDT after the introduction of PFDT side chains disappears significantly. This is because the introduction of fluorinated long chains destroys the regularity of the molecular chain, thereby inhibiting low-temperature crystallization and greatly improving the low-temperature performance of MVQ. DETAILED DESCRIPTION

[0038] The present invention will be described in detail below with reference to specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art to the present invention based on the contents of the present invention still fall within the scope of protection of the present invention.

[0039] The raw materials used in the examples of the present invention are all commercially available products, and their specific information is shown in Table 1 below:

[0040] Table 1

[0041]

[0042] Among them, methyl vinyl silicone rubber was prepared by referring to the existing technology: Zhang Weizhen. Synthesis of epoxidized silicone rubber and preparation and application research of its composite materials [D]. Beijing University of Chemical Technology, 2023. The specific preparation method is as follows:

[0043] 20 g of octamethylcyclotetrasiloxane (D4) and 0.4 g of tetramethylammonium hydroxide pentahydrate (TMAOH·5H2O) were added to a 100 ml three-necked flask and placed in a constant temperature oil bath at 80°C. First, a magnetic stirrer was added and nitrogen was introduced to remove air from the system for 5 minutes. After turning off the nitrogen, a vacuum pump was used to evacuate the system to a negative pressure of -0.098 MPa. The reaction was continued for 4 hours to obtain a viscous transparent catalyst. After natural cooling, the catalyst was poured into a brown reagent bottle, sealed and stored away from light.

[0044] D4 and tetramethyltetravinylcyclotetrasiloxane (V4) were added to a 1L round-bottom open reactor according to the ratios listed in Table 2 below. The reactor was then placed in an 80°C constant-temperature oil bath and stirred with a stainless steel impeller at 200 rpm. Nitrogen was introduced for 5 minutes to remove air from the system. The nitrogen was then turned off and the system was evacuated to -0.098 MPa to remove moisture. After 1.5 hours of dehydration, nitrogen was introduced to return the system to ambient pressure. The temperature was then raised to 113°C. The catalyst prepared above and decamethyltetrasiloxane (DMTS) end-capping agent were added. During the polymerization reaction, the impeller speed was gradually reduced to 10 rpm as the system viscosity changed. After 3 hours of polymerization, the temperature was raised to 163°C. The nitrogen was turned off and the system was slowly evacuated to -0.098 MPa to remove the catalyst and unreacted monomers. After 2.5 hours of impurity removal, the system was returned to ambient pressure. The system was cooled to room temperature and collected to obtain MVQ raw rubber. The specific reaction equation is shown below, and the formulation is shown in Table 2.

[0045]

[0046] Table 2

[0047]

[0048] Example 1

[0049] The vinyl content was 10.18 mol% and the molecular weight was 29.05×10 4MVQ (molecular quinoline, or MVQ) with a molecular weight distribution of 1.68 was added to THF at a concentration of 5g / 50ml and magnetic stirring was used to fully dissolve the mixture. PFDT (the molar ratio of PFDT to vinyl groups in MVQ was 1.2:1) was then added and stirred for 30 minutes. The photoinitiator, benzoin dimethyl ether (the molar ratio of benzoin dimethyl ether to vinyl groups in MVQ was 0.01:1) was then added. In a sealed chamber, the grafting reaction was initiated using a 365nm UV lamp. The magnetic rotation speed was 350 rpm, the grafting reaction lasted 5 minutes, and the reaction temperature was 22°C-25°C. After the grafting reaction, the reaction solution was poured into anhydrous ethanol for flocculation to obtain MVQ-g-PFDT. The volume ratio of anhydrous ethanol to the glue was 2:1. The mixture was then redissolved in THF and flocculated again to remove the initiator and unreacted small molecules. This process was repeated three times before the product was dried in a vacuum oven at 55°C to constant weight to remove the solvent.

[0050] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.37 mol%, and 9.81 mol%, respectively, that is, the PFDT side chain content was 9.81 mol%.

[0051] Example 2

[0052] The preparation method is basically the same as that in Example 1, except for the type of photoinitiator. The photoinitiator used is 2-hydroxy-2-methylphenylacetone, and the molar ratio of 2-hydroxy-2-methylphenylacetone to vinyl in MVQ is 0.01:1.

[0053] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.07 mol%, and 10.11 mol%, respectively, that is, the PFDT side chain content was 10.11 mol%.

[0054] Example 3

[0055] The preparation method is basically the same as that in Example 1, except for the type of photoinitiator. The initiators used are CBP and TPO, and the molar ratio of vinyl in methyl vinyl silicone rubber to CBP is 1:0.03; the molar ratio of vinyl in methyl vinyl silicone rubber to TPO is 1:0.01.

[0056] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.44 mol%, and 9.74 mol%, respectively, that is, the PFDT side chain content was 9.74 mol%.

[0057] Example 4

[0058] The preparation method is basically the same as that of Example 1, except for the reaction time of the grafting reaction, which is 1 min.

[0059] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.84 mol%, and 9.34 mol%, respectively, that is, the PFDT side chain content was 9.34 mol%.

[0060] Example 5

[0061] The preparation method is basically the same as that of Example 1, except for the reaction time of the grafting reaction, which is 10 min.

[0062] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.23 mol%, and 9.95 mol%, respectively, that is, the PFDT side chain content was 9.95 mol%.

[0063] Example 6

[0064] The preparation method is basically the same as that of Example 1, except for the reaction time of the grafting reaction, which is 15 min.

[0065] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.18 mol%, and 10.00 mol%, respectively, that is, the PFDT side chain content was 10.00 mol%.

[0066] Example 7

[0067] The preparation method is basically the same as that of Example 1, except that the concentration of the glue solution is 3g / 50ml.

[0068] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 1.17 mol%, and 9.01 mol%, respectively, that is, the PFDT side chain content was 9.01 mol%.

[0069] Example 8

[0070] The preparation method is basically the same as that of Example 1, except for the concentration of the glue solution, which is 4 g / 50 ml.

[0071] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.96 mol%, and 9.22 mol%, respectively, that is, the PFDT side chain content was 9.22 mol%.

[0072] Example 9

[0073] The preparation method is basically the same as that of Example 1, except that the concentration of the glue solution is 6 g / 50 ml.

[0074] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.37 mol%, and 9.81 mol%, respectively, that is, the PFDT side chain content was 9.81 mol%.

[0075] Example 10

[0076] The preparation method is basically the same as that of Example 1, except that the solvent type is dichloromethane and the concentration of the glue is 5g / 50ml.

[0077] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 1.07 mol%, and 9.11 mol%, respectively, that is, the PFDT side chain content was 9.11 mol%.

[0078] Example 11

[0079] The preparation method is basically the same as that of Example 1, except that the solvent type is chlorobenzene and the concentration of the glue solution is 5g / 50ml.

[0080] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 1.37 mol%, and 8.81 mol%, respectively, that is, the PFDT side chain content was 8.81 mol%.

[0081] Example 12

[0082] The preparation method is basically the same as that of Example 1, except for the amount of PFDT used. The molar ratio of PFDT to the vinyl group in MVQ is 0.8:1.

[0083] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 2.07 mol%, and 8.11 mol%, respectively, that is, the PFDT side chain content was 8.11 mol%.

[0084] Example 13

[0085] The preparation method is basically the same as that of Example 1, except for the amount of PFDT used. The molar ratio of PFDT to the vinyl group in MVQ is 1.5:1.

[0086] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.13 mol%, and 10.05 mol%, respectively, that is, the PFDT side chain content was 10.05 mol%.

[0087] Example 14

[0088] The preparation method is basically the same as that of Example 1, except for the amount of PFDT used. The molar ratio of PFDT to the vinyl group in MVQ is 3:1.

[0089] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.07 mol%, and 10.11 mol%, respectively, that is, the PFDT side chain content was 10.11 mol%.

[0090] Example 15

[0091] The preparation method is basically the same as that of Example 1, except that the amount of benzoin dimethyl ether is used, and the molar ratio of benzoin dimethyl ether to vinyl in MVQ is 0.005:1.

[0092] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 1.12 mol%, and 9.06 mol%, respectively, that is, the PFDT side chain content was 9.06 mol%.

[0093] Example 16

[0094] The preparation method is basically the same as that of Example 1, except that the amount of benzoin dimethyl ether is used, and the molar ratio of benzoin dimethyl ether to vinyl in MVQ is 0.02:1.

[0095] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.10 mol%, and 10.08 mol%, respectively, that is, the PFDT side chain content was 10.08 mol%.

[0096] Example 17

[0097] The preparation method is basically the same as that of Example 1, except that the amount of benzoin dimethyl ether is used, and the molar ratio of benzoin dimethyl ether to vinyl in MVQ is 0.05:1.

[0098] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.02 mol%, and 10.16 mol%, respectively, that is, the PFDT side chain content was 10.16 mol%.

[0099] Example 18

[0100] The preparation method is basically the same as that of Example 1, except that MVQ is selected, and the vinyl content of MVQ is 5.11 mol%, and the molecular weight is 27.47×10 4 , molecular weight distribution is 1.74.

[0101] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 94.89 mol%, 0.46 mol%, and 4.65 mol%, respectively, that is, the PFDT side chain content was 4.65 mol%.

[0102] Example 19

[0103] The preparation method is basically the same as that of Example 1, except that MVQ is selected, and the vinyl content of MVQ is 14.13 mol%, the molecular weight is 35.95×10 4 , molecular weight distribution is 1.58.

[0104] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 85.87 mol%, 2.83 mol%, and 11.30 mol%, respectively, that is, the PFDT side chain content was 11.30 mol%.

[0105] Example 20

[0106] The preparation method is basically the same as that of Example 1, except for the rotation speed of the magneton, which is 300 r / min.

[0107] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.83 mol%, and 9.35 mol%, respectively, that is, the PFDT side chain content was 9.35 mol%.

[0108] Example 21

[0109] The preparation method is basically the same as that of Example 1, except for the rotation speed of the magneton, which is 400 r / min.

[0110] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.22 mol%, and 9.96 mol%, respectively, that is, the PFDT side chain content was 9.96 mol%.

[0111] Example 22

[0112] The preparation method is basically the same as that of Example 1, except that the poor solvent for post-treatment is selected. The poor solvent is anhydrous methanol, and the volume ratio of anhydrous methanol to the glue solution is 2:1.

[0113] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.20 mol%, and 9.98 mol%, respectively, that is, the PFDT side chain content was 9.98 mol%.

[0114] Example 23

[0115] The preparation method is basically the same as that of Example 1, except that the amount of anhydrous ethanol used in the post-treatment is 1.5:1 by volume.

[0116] The integral area of ​​the corresponding structure in the H-NMR spectrum was used to calculate that the content percentages of x, y, and z corresponding to each repeating unit in MVQ-g-PFDT were 89.82 mol%, 0.19 mol%, and 9.99 mol%, respectively, that is, the PFDT side chain content was 9.99 mol%.

[0117] The properties of the MVQ-g-PFDT prepared in the examples were compared: PFDT side chain content was quantitatively calculated using proton nuclear magnetic resonance spectroscopy, followed by conversion, where conversion = post-reaction PFDT side chain content / pre-reaction vinyl content. The number average molecular weight and molecular weight distribution of MVQ-g-PFDT were determined using gel permeation chromatography (GPC). The results are shown in Table 3 below:

[0118] Table 3

[0119] sample Conversion rate / % <![CDATA[Molecular weight / 10 4 g / mol]]> Molecular weight distribution Example 1 96.39 29.91 1.75 Example 2 99.28 32.11 1.66 Example 3 95.69 32.42 1.62 Example 4 91.75 33.81 1.61 Example 5 97.75 28.15 1.81 Example 6 98.25 30.73 1.66 Example 7 88.51 28.92 1.77 Example 8 90.55 29.71 1.76 Example 9 96.39 29.78 1.76 Example 10 89.49 30.15 1.82 Example 11 86.54 29.68 1.88 Example 12 79.67 27.13 1.92 Example 13 98.72 29.34 1.74 Example 14 99.31 26.11 1.89 Example 15 89.00 28.85 1.74 Example 16 99.02 31.98 1.69 Example 17 99.80 32.23 1.65 Example 18 91.00 28.16 1.82 Example 19 79.97 38.26 1.93 Example 20 91.85 32.08 1.82 Example 21 97.84 29.01 1.79 Example 22 98.04 30.36 1.69 Example 23 98.13 29.68 1.78

[0120] Table 3 shows that when preparing MVQ-g-PFDT using different photoinitiators, 2-hydroxy-2-methylphenylacetone exhibits the best initiation efficiency, the highest conversion rate, and a narrower molecular weight distribution. Prolonging the reaction time and increasing the gel concentration both lead to improved conversion rates. Using tetrahydrofuran as the solvent achieves the highest conversion rate and the narrowest molecular weight distribution. The conversion rate increases with increasing PFDT dosage. However, excessive PFDT increases the acidity of the system, causing degradation of the siloxane backbone under the action of acid, resulting in a significant decrease in the molecular weight of MVQ-g-PFDT. Increasing the photoinitiator dosage can effectively improve the reaction conversion rate, but excess photoinitiator is difficult to remove during post-processing, resulting in reduced product purity and hindering the long-term storage of MVQ-g-PFDT. The choice and dosage of poor solvents used in post-processing have little significant impact on the reaction.

Claims

1. A fluorinated silicone rubber having the structural formula: in, x is 85-100 mol%, preferably 89-91 mol%; y is 0-5 mol%, preferably 0.05-2 mol%; z is 0-15 mol%, preferably 8-11 mol%.

2. A method for preparing the fluorinated silicone rubber according to claim 1, comprising: The methyl vinyl silicone rubber is dissolved in a solvent, and then perfluorodecanethiol and a photoinitiator are added. A grafting reaction is initiated in a closed environment using an ultraviolet light source. After the grafting reaction is completed, flocculation and drying are performed to obtain the fluorinated silicone rubber.

3. The preparation method according to claim 2, wherein: The vinyl content of the methyl vinyl silicone rubber is 5-15 mol%, preferably 9-11 mol%, and / or the number average molecular weight is (25-35)×10 4 g / mol, preferably (27-33)×10 4 g / mol, and / or, a molecular weight distribution of 1.0-2.0, preferably 1.5-1.

9.

4. The preparation method according to claim 2, wherein: The solvent is at least one of tetrahydrofuran, dichloromethane and chlorobenzene.

5. The preparation method according to claim 2, wherein: The photoinitiator is at least one of benzoin dimethyl ether, 2-hydroxy-2-methylphenyl acetone, 4-chlorobenzophenone, and 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide.

6. The preparation method according to claim 2, wherein: The concentration of the methyl vinyl silicone rubber after being dissolved in the solvent is 1-10 g / 50 ml, preferably 3-6 g / 50 ml.

7. The preparation method according to claim 2, characterized in that: The molar ratio of vinyl groups in the methyl vinyl silicone rubber to perfluorodecanethiol is 1:(0.8-3), preferably 1:(1.2-1.5).

8. The preparation method according to claim 2, wherein: The molar ratio of the vinyl group in the methyl vinyl silicone rubber to the photoinitiator is 1:(0.005-0.05), preferably 1:(0.01-0.02).

9. The preparation method according to claim 2, wherein: The reaction temperature of the grafting reaction is 22° C.-25° C., and / or the reaction time is 1-15 minutes.

10. A fluorinated silicone rubber prepared by the preparation method according to any one of claims 2 to 9.